Martensitic stainless steel material and application thereof in laser additive manufacturing

By regulating the composition distribution ratio of martensite stainless steel materials, reducing their phase change temperature, and using the solid-state phase change volume expansion effect, the residual stress control problem in laser additive manufacturing is solved, and the uniformity of stress distribution and high strength of parts are achieved. , improves the control and fatigue life of the repair area.

CN119194295APending Publication Date: 2024-12-27SUN YAT SEN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411246005.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Residual stress control is difficult to achieve in laser additive manufacturing, resulting in cracks, deformation and reduced strength of parts, affecting their service behavior and safety.

Method used

It provides a martensite stainless steel material, which reduces the martensite phase transition temperature by regulating the assembly distribution ratio of additive powder, and uses the solid-state phase change volume expansion effect to offset the shrinkage during cooling, so as to achieve in-situ adjustment of residual stress.

Benefits of technology

It effectively reduces residual tensile stress, improves the uniformity of stress distribution, improves the control and control of the repair area, extends the fatigue life of the parts, and reduces production costs and time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194295A_ABST
    Figure CN119194295A_ABST
Patent Text Reader

Abstract

The invention relates to a martensitic stainless steel material and application thereof in laser additive manufacturing, and belongs to the technical field of laser additive manufacturing. The martensitic stainless steel material provided by the invention comprises the following components in percentage by mass: 0.014 to 0.141 percent of C, 0.31 to 4.89 percent of Cu, 0.32 to 1.0 percent of Si, 10.16 to 16.2 percent of Cr, 0.6 to 1.2 percent of Mn, 3.8 to 8.11 percent of Ni, 0.1 to 0.5 percent of Nb, 0.01 to 0.03 percent of P, 0 to 0.22 percent of Mo and the balance of Fe. The martensitic stainless steel material provided by the invention has a lower phase transition temperature, is used in additive remanufacturing, can improve the residual stress of an additive remanufacturing repair area of high-strength low-alloy steel, generates residual compression stress in the repair area and the range nearby the repair area, and achieves the purposes of shape control and property control; the method has extremely high value in application in the fields of national defense and military industry and aerospace additive manufacturing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of laser additive manufacturing, and in particular to a martensitic stainless steel material and an application thereof in laser additive manufacturing. Background Art

[0002] Laser additive manufacturing technology is a new type of rapid prototyping technology that can quickly and accurately process high-quality complex structure products. The use of laser additive technology in the repair process of parts is called laser additive remanufacturing. Due to its low time consumption, low cost, high efficiency and excellent mechanical properties, the application of laser additive remanufacturing technology in national defense and military industry, aerospace, automobile, petroleum, chemical industry and other fields has gradually gained attention.

[0003] The laser energy density is concentrated. During the cladding forming process, the temperature and physical properties of the material are extremely non-uniform. The complex thermal cycle is accompanied by the inevitable evolution of stress and strain, which may cause cracks and deformation of parts or even scrap. The high residual stress state may also reduce the strength of the material, induce stress corrosion and shorten the fatigue life, ultimately affecting the service behavior and safety of the remanufactured parts. Traditional residual stress control processes include increasing the thermophysical property matching between the substrate and the welding material, reducing the laser cladding line energy, etc. These methods are limited by actual working conditions, requirements for the service performance of parts, production costs and efficiency, and are difficult to be applied in the production of some large and important parts.

[0004] Solid-state phase transformation may have a dominant influence on the stress evolution of laser cladding forming or other welding processes. Jones and Alberry studied the use of volume expansion generated by the transformation of austenite to martensite to offset the volume contraction during welding cooling to control the stress and strain of the welded joint. Ohta et al. used Cr and Ni to control the transformation temperature of martensite and applied it to low-carbon steel materials. KAWADA used this low phase transformation temperature welding wire for non-modulated steel joints, and the fatigue life was increased by 2-4 times. However, currently low phase transformation temperature materials are mainly used in welding processes. The field inhomogeneity, stress level, stress distribution inhomogeneity, and nonlinearity in laser additive manufacturing and remanufacturing processes are quite different from those in the same welding process, which leads to some unimportant factors in the welding process being highlighted in the laser additive manufacturing process.

[0005] Therefore, it is of great significance to develop a method to control residual stress in laser additive manufacturing and remanufacturing in order to improve the residual stress in the repair area, make the stress distribution uniform, and achieve the purpose of shape control and property control, which is of great significance to the further development and application of laser additive manufacturing technology. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a martensitic stainless steel material and its application in laser additive manufacturing. The martensitic stainless steel material provided by the present invention is applied in laser additive manufacturing and additive remanufacturing, and can realize in-situ adjustment of residual stress of high-strength low-alloy steel, and has high application value.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] In a first aspect, the present invention provides a martensitic stainless steel material, comprising the following components, in mass percentage: 0.014-0.141% C, 0.31-4.89% Cu, 0.32-1.0% Si, 10.16-16.2% Cr, 0.6-1.2% Mn, 3.8-8.11% Ni, 0.1-0.5% Nb, 0.01-0.03% P, 0-0.22% Mo, and the balance is Fe.

[0009] The present invention limits the component ratio of martensitic stainless steel materials, and controls the solid-state phase transformation process of the material by regulating the martensitic transformation temperature of the additive powder: the material of the present invention has a low martensitic transformation temperature (<250°C), the start and end temperatures of the martensitic transformation that occurs in the material during the cooling process are relatively low, and the volume expansion caused by the phase transformation of the material is retained, thereby effectively reducing the residual tensile stress and realizing in-situ regulation of the residual stress.

[0010] Under the above-mentioned limited component ratio, martensitic stainless steel materials have significant advantages over ordinary alloy powders. The solid-state phase transformation produced by the cooling process of ordinary alloy materials is not retained to room temperature, so it does not bring about the effect of offsetting thermal shrinkage and reducing residual tensile stress; changing the component ratio of the material outside the limited range may lead to a significant increase in the residual tensile stress when it is used in laser additive manufacturing, which means that in the rapid cooling process from high temperature to low temperature in laser additive manufacturing, uneven plastic deformation of the material may occur due to the uneven temperature field; in the subsequent process of the temperature field returning to uniformity, the area where stress exists cannot be freely expanded and contracted due to the constraints of the surrounding area, which is not conducive to the shape and property control of the additive remanufacturing repair area.

[0011] The martensitic stainless steel material provided by the present invention can be applied to laser additive manufacturing and additive remanufacturing (repair), and the volume expansion effect generated by solid phase change can be used to offset the contraction of the laser additive remanufactured sample during the cooling process, thereby achieving residual stress and deformation control of the overall repaired part. Compared with large parts that are not suitable for heat treatment, and parts made of certain materials are prone to performance failure during heat treatment, especially some parts will deform and crack due to residual stress during the production process. The martensitic stainless steel material provided by the present invention is suitable for repairing various types of materials and large parts, including metals, ceramics and composite materials, and has extremely high application value.

[0012] Preferably, the following components are included in mass percentage: 0.07-0.041% C, 4.29-4.5% Cu, 0.76-1.0% Si, 15.5-15.98% Cr, 0.64-1% Mn, 4.29-5.5% Ni, 0.3-0.4% Nb, 0.01-0.015% P, and the balance is Fe.

[0013] Further preferably, the alloy comprises the following components, in mass percentage: 0.041% C, 4.29% Cu, 0.76% Si, 15.98% Cr, 0.64% Mn, 4.29% Ni, 0.37% Nb, 0.015% P, and the balance is Fe.

[0014] Under the preferred composition ratio of martensitic stainless steel material, when applied in additive remanufacturing, the residual tensile stress near the repair area can be converted into residual compressive stress that is beneficial to the fatigue strength of the repaired sample, and the residual stress distribution of the parts after additive remanufacturing can be more effectively improved.

[0015] Preferably, the martensitic stainless steel material is prepared by an aerosol method.

[0016] Further preferably, the aerosol method is: smelting or mechanically milling a metal raw material to obtain an alloy material, heating and melting the alloy material, and then atomizing and cooling the alloy material using a high-speed gas flow to obtain the martensitic stainless steel material. The powder prepared by this method has uniform composition, high sphericity, and good fluidity.

[0017] Further preferably, the particle size of the martensitic stainless steel material is 53 μm-150 μm. The martensitic stainless steel material powder within this particle size range prepared by the aerosol method can better meet the needs of further application in the field of additive manufacturing.

[0018] Preferably, the phase transition temperature of the martensitic stainless steel material is less than 250°C.

[0019] In a second aspect, the present invention provides an application of the above-mentioned martensitic stainless steel material in additive manufacturing, wherein the application includes laser additive manufacturing.

[0020] Among them, laser additive manufacturing can be direct additive manufacturing, and can also be further applied to laser additive manufacturing repair (additive remanufacturing) of various materials.

[0021] Preferably, the laser additive manufacturing comprises the following steps:

[0022] In an inert atmosphere, the martensitic stainless steel material according to any one of claims 1 to 6 is deposited on a substrate by a laser melting process, and then the surface is polished by an electrolytic polishing process to complete the laser additive manufacturing.

[0023] The present invention uses the above-mentioned martensitic stainless steel material combined with the laser melting process for additive remanufacturing, which can realize the in-situ regulation of residual stress and deformation of the repaired parts based on solid-state phase transformation; at the same time, through the laser melting process, the residual stress can be adjusted in a shorter time, thereby improving production efficiency and reducing production costs.

[0024] Further preferably, in the laser melting process, the laser power is 1300-1500 W and the scanning rate is 800-1000 mm / min.

[0025] Further preferably, in the electrolytic polishing process, the electrolyte is a NaCl solution with a mass concentration of 3-4%, the electrolytic polishing voltage is a constant voltage of 30-35V, and the electrolytic polishing time is 1-3min.

[0026] By optimizing and controlling the laser process parameters, reducing the impact of internal holes and crack defects on residual stress analysis, and combining the characteristics of the above-mentioned martensitic stainless steel materials, the in-situ adjustment of residual stress can be better achieved.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The present invention obtains martensitic stainless steel material by optimizing the composition of low phase transition temperature alloy powder, controls the lower martensitic transformation temperature, and regulates the solid-state phase transition process. The martensitic stainless steel material can be further used in additive manufacturing by laser melting process. Combined with a specific laser additive manufacturing process, the volume expansion effect produced by the solid-state phase transition is used to offset the shrinkage of the laser additive remanufactured sample during the cooling process, thereby achieving residual stress and deformation control in the additive remanufacturing repair area of ​​high-strength low-alloy steel and other materials, thereby improving the "first bottleneck problem" of residual stress in laser additive manufacturing applications, and has great value in the further research and application of laser additive manufacturing. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1The figure is a schematic diagram of the morphology of the substrate to be repaired and the residual stress test position in the effect example;

[0030] Figure 2 The longitudinal residual stress distribution result diagram at different positions deviating from the repair center after additive repair using the materials of the embodiment and the comparative example;

[0031] Figure 3 a Continuous Cooling Transformation (CCT) curve of the martensitic stainless steel material in Example 1; b Expansion Cooling Curve during the heating and cooling cycle.

[0032] Figure 4 It is a finite element simulation distribution cloud diagram of the longitudinal residual stress field of the sample repaired by the materials of Example 1 and Comparative Example 4. DETAILED DESCRIPTION

[0033] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below in conjunction with specific examples. The test methods used in the following examples are conventional methods unless otherwise specified; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.

[0034] Examples 1-3 and Comparative Examples 1-4

[0035] Examples 1-3 are three different examples of the martensitic stainless steel material provided by the present invention; Comparative Examples 1-4 are comparative alloy materials with different proportions.

[0036] The preparation methods of the materials in Examples 1-3 and Comparative Examples 1-4 are all aerosol methods:

[0037] After mixing the various metal raw materials through mechanical ball milling and obtaining a uniform alloy material, the material is placed in the crucible of the smelting furnace. The smelting furnace is evacuated to a vacuum degree of <10Pa, filled with argon gas to atmospheric pressure, and heated to 900°C to melt the mixed raw materials in the crucible into molten metal and keep it warm for a period of time until the molten metal is completely alloyed. After the alloy liquid is poured from the crucible into the preheated tundish, it enters the atomization zone through the guide pipe at the bottom of the center package, and the alloy liquid is impacted by high-pressure and high-speed argon gas to break it into metal droplets, and gradually solidify into metal powder. The atomization pressure is 2.5MPa. After the atomization is completed, the metal powder is collected and the powder is classified by screening equipment to prepare an alloy material powder with a particle size of 53μm-150μm.

[0038] The mass percentages of the material components in Examples 1-3 and Comparative Examples 1-4 are shown in Table 1.

[0039] Table 1 Mass percentage of material components in the embodiments and comparative examples

[0040]

[0041] Effect example

[0042] In order to explore the application effect of the martensitic stainless steel material provided by the present invention in laser additive remanufacturing, the substrates repaired by the materials in Examples 1-3 and Comparative Examples 1-4 are rolled HSLA-100 high-strength low-alloy steel, wherein the composition content of the HSLA substrate is shown in Table 2, and the specific test steps are as follows:

[0043] (1) A trapezoidal notch with a bottom angle of 120° and a depth of 5 mm is pre-cut on a HSLA-100 high-strength low-alloy steel substrate with a size of 200 mm*65 mm*20 mm. Figure 1 : Area A in the figure is the substrate additive repair area;

[0044] (2) After the substrate was surface treated with sandpaper, the substrate was repaired by laser additive manufacturing using the material powders in the embodiment and the comparative example: a laser melting process (LMD) was used, and the substrate was deposited along the width direction during printing, and then accumulated layer by layer; the laser printing parameters were: laser power 1400 W, scanning rate 900 mm / min; the entire additive process was carried out under an argon atmosphere to prevent oxidation of the sample;

[0045] (3) After printing is completed, the surface is polished using an electrolytic polishing process to remove the surface stress layer: the electrolytic polishing process uses an electrolyte with a mass concentration of 3.5% NaCl in a 32V constant voltage mode, and the polishing time is 2 minutes. The polished surface is then wiped with alcohol and air-dried to complete the repair;

[0046] (4) A residual stress test was performed on one side of the middle position on the upper surface of the repair groove. The test points extended along the length direction of the substrate, and a total of 5 test points were selected. In order to avoid experimental errors, the experiment was repeated on the side of the repair area close to the substrate, and the test data was compared and verified with the previous test data. The X-ray diffraction method was used for this residual stress test, which is non-destructive to the test object. The test instrument used was the μ-X360 portable X-ray residual stress tester. The test ray selected the Ka target and tested each point in the XY direction. Figure 1 The marked points 1-5 in the figure are the test positions of residual stress, and the interval between each test point is 2 mm;

[0047] (5) A finite element simulation model for residual stress calculation in the additive remanufacturing process is further established. The model takes into account the influence of temperature-dependent material thermophysical parameters and solid phase transition. A nonlinear thermomechanical coupling model is used to calculate the law of residual stress variation under different physical parameters, and the simulation results are analyzed.

[0048] The longitudinal residual stress distribution and comparison of different positions (2, 4, 6, 8, 10 mm) deviating from the repair center after repair using the materials in Examples 1-3 and Comparative Examples 1-4 are shown in Tables 3 and Figure 2 Considering the influence of temperature field distribution and organizational transformation, the finite element simulation distribution cloud diagram of the longitudinal residual stress field of the additive repair sample using the materials of Example 1 (right) and Comparative Example 4 (left) is as follows Figure 4 .

[0049] From Table 1 and Figure 2 It can be seen that:

[0050] From the comparison of the residual stress at different positions deviating from the repair center after additive repair, it can be seen that, compared with the different alloy materials whose components are outside the limited range in the comparative example, the novel martensitic stainless steel material provided by the present invention has lower residual stress at different positions deviating from the repair center after additive repair, and the distribution is more uniform, which is more conducive to the control of shape and property of the repair area and its vicinity after repair;

[0051] Among them, the martensitic stainless steel material of Example 1 has the best control effect on residual stress: after additive repair, as the distance from the center of the repair area increases, the residual tensile stress decreases, and turns into residual compressive stress after 6 mm; compared with the ordinary alloy material GH3536, it has lower residual tensile stress. The solid phase transformation produced by the cooling process of the ordinary alloy material is not retained to room temperature, so it does not bring about the effect of offsetting thermal shrinkage and reducing residual tensile stress;

[0052] The martensitic stainless steel material in Example 1 was measured to obtain its continuous cooling transformation (CCT) curve and expansion cooling curve during the heating and cooling cycle. The results are as follows: Figure 3 -a and 3-b.

[0053] Combining the above results and Figure 3 It can be seen that the start and end temperatures of the martensitic phase transformation occurring during the cooling process of the martensitic stainless steel material provided by the present invention are relatively low, and the volume expansion caused by the phase transformation of the material is retained, thereby being able to well reduce the residual stress attached to the repair area, and to generate residual compressive stress beneficial to the fatigue strength of the repaired sample on the surface near the repair area, thereby effectively improving the residual stress distribution of the parts after additive remanufacturing, greatly reducing the magnitude of the residual tensile stress, and even within the preferred range, being able to convert the residual tensile stress near the repair area into residual compressive stress.

[0054] Depend on Figure 4 It can be seen that:

[0055] The volume expansion effect of the martensitic stainless steel material provided by the present invention due to the formation of a large amount of residual martensite after cooling partially offsets the thermal contraction effect of the central area of ​​the molten pool during cooling, thereby causing a significant change in the residual stress distribution near the molten pool. In fact, the residual stress in most areas near the molten pool of the martensitic stainless steel material powder is significantly lower than that of the sample repaired with conventional GH3536 powder in Comparative Example 4.

[0056] The simulation results further prove that the martensitic stainless steel material provided by the present invention can effectively control the residual stress distribution of additive repair and significantly improve the shape and property control effects of the repair material. It can be used in laser additive repair of high-strength low-alloy steel, and can effectively control and improve stress levels, uneven stress distribution and other problems, and has extremely high application value.

[0057] Table 2 Component contents of the HSLA substrate to be repaired

[0058]

[0059]

[0060] Table 3 Residual stress results at different positions deviating from the repair center after additive repair using materials of the embodiment and comparative example

[0061]

[0062] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A martensitic stainless steel material, characterized in that: Calculated by mass percentage, it includes the following components: 0.014-0.141% C, 0.31-4.89% Cu, 0.32-1.0% Si, 10.16-16.2% Cr, 0.6-1.2% Mn, 3.8-8.11% Ni, 0.1-0.5% Nb, 0.01-0.03% P, 0-0.22% Mo, and the balance is Fe.

2. The martensitic stainless steel material according to claim 1, characterized in that: Calculated by mass percentage, it includes the following components: 0.07-0.041% C, 4.29-4.5% Cu, 0.76-1.0% Si, 15.5-15.98% Cr, 0.64-1% Mn, 4.29-5.5% Ni, 0.3-0.4% Nb, 0.01-0.015% P, and the balance is Fe.

3. The martensitic stainless steel material according to claim 2, characterized in that: Calculated by mass percentage, it includes the following components: 0.041% C, 4.29% Cu, 0.76% Si, 15.98% Cr, 0.64% Mn, 4.29% Ni, 0.37% Nb, 0.015% P, and the balance is Fe.

4. The martensitic stainless steel material according to claim 1, characterized in that: The preparation method of the martensitic stainless steel material is an aerosol method.

5. The martensitic stainless steel material according to claim 4, characterized in that: The particle size of the martensitic stainless steel material is 53 μm-150 μm.

6. The martensitic stainless steel material according to claim 1, characterized in that: The phase transition temperature of the martensitic stainless steel material is less than 250°C.

7. The use of the martensitic stainless steel material according to any one of claims 1 to 6 in additive manufacturing, characterized in that: The applications include laser additive manufacturing.

8. The use of the martensitic stainless steel material in additive manufacturing according to claim 7, characterized in that: The laser additive manufacturing comprises the following steps: In an inert atmosphere, the martensitic stainless steel material according to any one of claims 1 to 6 is deposited on a substrate by a laser melting process, and then the surface is polished by an electrolytic polishing process to complete the laser additive manufacturing.

9. The use of the martensitic stainless steel material in additive manufacturing as claimed in claim 8, characterized in that: In the laser melting process, the laser power is 1300-1500W and the scanning rate is 800-1000mm / min.

10. The use of the martensitic stainless steel material in additive manufacturing according to claim 8, characterized in that: In the electrolytic polishing process, the electrolyte is a NaCl solution with a mass concentration of 3-4%, the electrolytic polishing voltage is a constant voltage of 30-35V, and the electrolytic polishing time is 1-3min.